Equisetum ×meridionale (Milde) Chiov. – a new hybrid taxon in the flora of Poland - Tlałka, Dariusz; Sliwinska, Elwira; Kruk, Jerzy (Biodiversity: Research and Conservation, 2022)
A new hybrid within the Hippochaete subgenus of Equisetum genus, Equisetum ×meridionale (Milde) Chiov. was discovered in Poland during the research conducted in 2022 at two locations in Kotlina Żywiecka (the Żywiec Basin) and Beskid Wyspowy (Island Beskids – Western Beskids) in the anthropogenic habitats in close proximity to Equisetum ramosis-simum. The identity of the hybrid was unequivocally confirmed by macro-morphological observations, microscopic analysis and flow cytometry. The most pronounced macroscopic characteristics of the hybrid were the intermediate size of the shoots and leaf sheaths, which are black with long black teeth. The microscopic observations revealed that the hybrid has silica tubercles in the form of cross-bands, similarly as in the case of E. ramosissimum, but not in the form of two rows as in the case of E. variegatum. The measurements of the nuclear DNA content (2C values) revealed that the putative hybrid had a nuclear DNA content intermediate to that of the parental species, i.e. E. ramosissimum (56.13 pg) and E. variegatum (63.80 pg) obtained in the present studies and within the values previously reported for E. ×meridionale (60.7-61.2 pg).